PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVERNING (Studi Kasus Pada Karyawan PT Telekomunikasi Indonesia, Tbk Witel Kediri) - Andryane Andryane; Rahmayuni Rahmayuni; Mukaffi Zaim (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
Human resources are the driving force of an organization in achieving its objectives. So that employees who have good performance are needed to achieve the goals set by the company. To achieve good performance, support from the company's leadership is needed for employees. Support given by the leader can be in the form of appropriate compensation as rewards for employee performance. In addition, good performance can also be formed by creating good work discipline. This study aims to determine how the direct or indirect effect of compensation on employee performance through work discipline as an interverning variable. The object of this research is the employees of PT Telekomunikasi Indonesia, Tbk Witel Kediri. The sample used in this study amounted to 45 people. The sampling technique used is the saturation sampling technique. The dependent variable in this study is employee performance (Y), the independent variable is compensation (X), and the interverning variable used is work discipline (Z). The data analysis test tool in this study uses Path Analysis. The results showed that direct compensation had a significant effect on employee performance at PT Telekomunikasi Indonesia, Tbk Witel Kediri. This can be seen from the significant value of 0.013 <0.05. The results of the study also showed that compensation indirectly had a significant effect on employee performance through work discipline. This can be seen from the significant value of 0.001 <0.05